A new species of Chiridurothrips Okajima from Miocene amber of the Dominican Republic (Thysanoptera: Phlaeothripidae) - Ulitzka, Manfred R. (Zootaxa, 2019)
The thysanopteran genus Chiridurothrips Okajima is known from a single extant species, C. hisakoae Okajima, collected in Japan (ThripsWiki 2019). Occurring on dead leaves and branches of evergreen trees in the subtropical Ryukyu Islands, this species remains known from only five females (Okajima 1981, 2006; also pers. comm. 2018). Within Phlaeothripidae, Chiridurothrips is associated with the tribe Plectrothripini. Species of this sub-group feed on fungal hyphae or the break-down products of fungal attack on decaying plant material (Mound & Ng 2018). They are found mainly under the bark of trees or on dead branches, and they do not seem to inhabit leaf-litter (Okajima 1981). At present, Plectrothripini comprises 60 extant species in 13 genera, with no fossils recorded. Of these species 32 are placed in the genus Plectrothrips Hood, ten in Streptothrips Priesner, and six in Chirothripoides Bagnall, whereas both Menothrips Hood and Mastigothrips Priesner each include only two species. The remaining eight species are all placed in separate monobasic genera (ThripsWiki 2019). Concerning this strongly asymmetric classification, Mound and Ng (2018) suggest that Plectrothripini might be particularly old, with the large number of monobasic genera each representing a relict lineage. An alternative possibility, however, might be an unusual instability in the genes controlling morphogenetic processes, and thus resulting in striking autapomorphies on which each one of these genera is diagnosed (Mound & Ng 2018). Species associated with Plectrothripini share the following character states (Okajima 1981; Mound & Tree 2017): antennae 8-segmented, segment II with the campaniform sensillum situated in the basal half, III–IV with stout sense cones, VIII slender with narrow base; head with posterior ocelli close to compound eyes; pronotum commonly with sclerotized plate eroded or reduced, prosternal basantra week or absent; legs with fore tarsal tooth large; mid and hind tibiae commonly with apical spur-like setae; macropterae with fore wings parallel-sided, usually with duplicated cilia; pelta broad at base, abdominal tergite II eroded laterally; abdominal sternites often with reticulate glandular areas. Regarding the fore wings, it seems worth mentioning that in some members of Plectrothripini the subbasal wing vein is reduced and thus the three subbasal wing setae are lacking (see Plectrothrips tenuis Okajima, Chiridurothrips [c.f. fig. 2], Chirothripoides, Lonchothrips Hood; Bhatti 1998; Okajima 1981). This short vein that is present in (almost all) other macropterous Phlaeothripidae has been interpreted as a plesiomorphic feature that resulted from the reduction of a former well-developed longitudinal first vein of ancestral Tubulifera, the Rohrthripidae (Ulitzka 2018, 2019).